2015
DOI: 10.18775/ijied.1849-7551-7020.2015.11.2007
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of disabled people in microfinance institutions: Where does Bangladesh stand?

Abstract: This article constitutes a summary of the literatures and practices on the microfinance industry and its contribution, the status of people with disabilities (PWDs), and the case studies for financial inclusion in Bangladesh. Many Microfinance Institutions (MFIs) are operating to serve all segments of the clients for financial inclusion. People with Disabilities encounter several exclusions in the mainstream microfinance institutions in Bangladesh. At the same time, MFIs faces numerous challenges to serve thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…While Sarker ( 2015 , 2020 ) argues that generally people with disabilities experience oppression and discrimination, it became apparent from this study that people with disabilities are experiencing further exclusions and mental stress during the COVID‐19 pandemic. Multiple studies (see Devkota et al, 2021 ; Poudel & Subedi, 2020 ) in Nepal found that COVID‐19 created severe mental health issues.…”
Section: Discussionmentioning
confidence: 74%
“…While Sarker ( 2015 , 2020 ) argues that generally people with disabilities experience oppression and discrimination, it became apparent from this study that people with disabilities are experiencing further exclusions and mental stress during the COVID‐19 pandemic. Multiple studies (see Devkota et al, 2021 ; Poudel & Subedi, 2020 ) in Nepal found that COVID‐19 created severe mental health issues.…”
Section: Discussionmentioning
confidence: 74%
“…Es por ello que urge que las estrategias sean concertadas en relación a los servicios que demandan la población con discapacidad en determinados sectores poblacionales. Es por ello que las entidades financieras deben preparar productos y servicios especializados según las necesidades de cada uno de ellos y así poder establecer una relación adecuada entre las organizaciones sean éstas públicas o privadas en beneficio del desarrollo social y económico de la población tal como lo señala Sarker (2015).…”
Section: Discussionunclassified
“…El mismo autor señala que es importante que los organismos gubernamentales apoyen este tipo de iniciativas del sector privado con la intención de poder acomodar los servicios que se ofertan a los ciudadanos con discapacidad física de cualquier tipo. Por otro lado, (Sarker, 2015), concluye que la incorporación de personas con discapacidad mediante instituciones de microfinanzas desarrolla oportunidades que pueden ser aprovechadas para la mejora de la calidad de vida de las mismas. El mismo autor señala que es importante la difusión de los mecanismos de microfinanzas en este segmento de la población, debido al hecho de que pueden generar una articulación entre los esfuerzos sociales de entidades gubernamentales y la capacidad de accesibilidad que puede tener una institución financiera.…”
Section: Políticaunclassified
“…PWD also face difficulties to get access into microfinance institutions e.g. discrimination and less access to credit as in majority cases, service providers undermine their capacity to engage in income generating activities and lack of willing and trust to serve them (Sarker, 2015).…”
Section: Exclusion From Income and Resourcesmentioning
confidence: 99%